2011
DOI: 10.1038/nmeth.1774
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine fluorophore derivatives with enhanced photostability

Abstract: Fluorescence applications requiring high photostability often depend on the use of solution additives to enhance fluorophore performance. Here we demonstrate that the direct or proximal conjugation of cyclooctatetraene (COT), 4-nitrobenzyl alcohol (NBA) or Trolox to the cyanine fluorophore Cy5 dramatically enhanced fluorophore photostability without otherwise affecting its native spectral characteristics. Such conjugation is a powerful means of improving the robustness of fluorescence-based applications demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
349
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(370 citation statements)
references
References 19 publications
18
349
2
1
Order By: Relevance
“…2). The signal-to-noise ratios (SNRs) (22,23) for continuous single-molecule fluorescence of the four dyes on the custom RS are comparable with the SNRs measured on our in-house built TIRF (3.18 for Cy3, 4.90 for Cy3.5, 2.64 for Cy5, and 3.05 for Cy5.5) under our measurement conditions ( Fig. 3 and SI Materials and Methods).…”
Section: Significancesupporting
confidence: 76%
“…2). The signal-to-noise ratios (SNRs) (22,23) for continuous single-molecule fluorescence of the four dyes on the custom RS are comparable with the SNRs measured on our in-house built TIRF (3.18 for Cy3, 4.90 for Cy3.5, 2.64 for Cy5, and 3.05 for Cy5.5) under our measurement conditions ( Fig. 3 and SI Materials and Methods).…”
Section: Significancesupporting
confidence: 76%
“…Akin to earlier steady state measurements of ternary complex formation (16), the fluorescence-based assays described here are based on changes in relative fluorescence intensity. However, unlike earlier work, the approach we describe is based on the environmentally sensitive Cy3 fluorophore (43,58) at a distinct site of tRNA attachment, the naturally occurring modified nucleotide acp 3 U present at position 47 in E. coli tRNA Phe . Although this modification is not as ubiquitous as the s 4 U residue utilized previously, tRNA molecules modified at this site have been shown to be fully functional in all aspects of the translation process, including aminoacylation, tRNA selection, and translocation (43,46,60).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these fluorescent probes suffer from some defects such as photobleaching of fluorescent dye, high toxicity and expensive cost of noble metal sources, [18][19][20][21] which has further restricted their widespread application. Fortunately, it has been reported that the poly(amide amine) (PAMAM) dendrimers can emit strong fluorescence under suitable conditions, 22,23 and represent a new class of competitive material because of their autofluorescence and other prominent properties including favorable water solubility, biocompatibility, and nonimmunogenic and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%